Click chemistry modification of copolymers with cysteine amino acid: tunable thermal, electrical properties and kinetic analysis - Toprak, Ali; Biryan, Fatih; Caliskan, Eray; Koran, Kenan (Springer, 2024)
This study presents a novel approach to modifying copolymers with active azide end-groups through click chemistry, specifically targeting the incorporation of cysteine amino acid. The synthesis commenced with the reaction between cysteine amino acid and propargyl amine, yielding the alkyne-terminated amino acid Boc-Cys(Bnz)-PA compound. Through the click chemistry methodology, the copolymer with active azide ends was modified with alkyne-terminated Cys-PA. Thermal characterization of the copolymers was performed via differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). DSC measurements revealed an increase in glass transition temperature (Tg) from 65 degrees C to 83 degrees C upon the modification with cysteine, indicating enhanced thermal stability. However, TGA data suggested a decrease in thermal stability as evidenced by lower initial degradation temperatures for the modified copolymer compared to the unmodified counterpart.The degradation activation energies of the copolymers were estimated using the Flynn-Wall-Ozawa method across various conversion ranges, demonstrating higher thermal degradation activation energy for the modified copolymer compared to the unmodified one. Dielectric behavior analysis conducted at room temperature over a frequency range from 100 Hz to 20 kHz revealed a decreasing trend in dielectric constant and dielectric loss values with increasing frequency for all copolymer structures. The alternating current (AC) conductivities at 30 kHz were calculated as 1.84 x 10-7 S cm-1, and 4.75 x 10-7 S cm-1 for P(VBCl-co-VBN3 0.77) and (P(VBCl-co-(VBN3-click-Cys)0.77), respectively, indicating a frequency-dependent conductivity enhancement with increasing frequency. Overall, the results suggest that these polymeric materials, containing amino acid structures, hold promise as dielectric materials for low-frequency and low-voltage devices such as sensors, owing to their tunable thermal and dielectric properties achieved through click chemistry modification.
Keywords: Polymer synthesis; Modification; Click chemistry; Dielectric properties; Thermal properties